Social Sustainability in Late Adolescence: Trait Emotional Intelligence Mediates the Impact of the Dark Triad on Altruism and Equity - Marco Giancola; Massimiliano Palmiero; Simonetta D’Amico (Frontiers in Psychology, 2022)
Adolescence involves a profound number of changes in all domains of development. Among others, adolescence yields an enhanced awareness and responsibility toward the community, representing a critical age to develop prosocial behaviors. In this study, the mediation role of Trait Emotional Intelligence (TEI) was detected for the relationship between the dark triad and prosocial behavior based on altruism and equity. A total of 129 healthy late adolescents filled in the Dark Triad Dirty Dozen, measuring Machiavellianism, psychopathy, and narcissism; the Altruistic Action Scale, evaluating behaviors directed at helping others; the Equity Scale, assessing behaviors directed at equity in different forms; and the TEI Questionnaire-Short Form. Results showed that TEI mediated the negative effects of the three dark triad traits on both altruism and equity. This finding suggests that TEI, which relies on a set of dispositions (e.g., emotional management of others, social competence, and empathy), might reduce the malevolent effects of the dark triad on altruism and equitable behavior in late adolescence. This led to assume that intervention programs focused on improving emotional skills, also in late adolescence, can promote prosociality.